СONE BEAM COMPUTED TOMOGRAPHY AS A METHOD OF ANATOMICAL AND FUNCTIONAL IDENTIFICATION OF MAXILLARY AND MANDIBULAR BONE CHANGES - Yulian Kukhlevskyy (Праці Наукового товариства імені Шевченка. Медичні науки, 2018)
Abstract: Osteoporosis is among the most common lifestyle diseases. Abnormal Ca2+ functioning is ones of the key factors of abnormal bone mineral density (BMD) despite its physiological background is still unknown. Cone beam computed tomography (CBCT) is used to determine the 3D and cross sectional images, as well as the quality of craniofacial bone structures through the resolve of BMD, based on gray scales Hounsfield Units values of the obtained images.